Establishing a Health Sciences writing centre in the changing landscape of South African Higher Education - Muna, Natashia; Hoosen, Taahira Goolam; Moxley, Karis; van Pletzen, Ermien (Critical Studies in Teaching and Learning, 2023)
This article describes, analyses, and reflects on the conceptualisation and establishment of a Writing Lab at a South African university’s Faculty of Health Sciences. Drawing on the theoretical framework of New Literacy Studies, the academic literacies approach, and South African writing centre scholarship, the analysis revealed that the conceptualisation of the Writing Lab was primarily informed by the academic socialisation model but has since shifted to encompass a more transformative ideology; opening spaces where students’ own knowledges and literacies practices could contribute to new forms of thinking and representation in the academy. We argue that the shift was facilitated by collaboration with disciplinary lecturers, the faculty’s Primary Health Care ethos, and the Writing Lab’s engagement with a large postgraduate population, leading to the Writing Lab’s participation in new forms of knowledge-building that could contribute to the creation of decolonised spaces and shifts in institutional culture.